Optimization of mass spectral features in MALDI-TOF MS profiling of Acinetobacter species - Šedo, Ondrej; Voráč, Aleš; Zdráhal, Zbyněk (Systematic and applied microbiology, 2011)
The influence of the matrix solution, sample form and deposition technique on the quality MALDI-TOF mass spectra was examined and assessed with the aim to improve MALDI-TOF MS performance for the identification of microorganisms and to enable automatic spectra acquisition. It was observed that the use of matrix compounds ferulic and sinapinic acid may result in improved mass spectral features, in terms of signal resolution and S/N ratio, as compared to alpha-cyano-4-hydroxycinnamic acid, which was, on the other hand, found to be the only matrix compound that enabled fully automatic mass spectra acquisition. The robustness of the whole sample preparation procedure was then assessed on a set of 25 strains of four Acinetobacter species. Results showed reproducible detection of subtle mass spectral differences between strains belonging to the same species, although they do not confirm the possibility of reliable strain typing.
Keywords: Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Acinetobacter; Bacteriological Techniques; bakteriologické techniky; spektrometrie hmotnostní - ionizace laserem za účasti matrice